Paperbacks: August. - Broadhurst, Sarah (Bookseller, 2005)
The article focuses on the books to be published in the August 2005. Some of these are--"Fleshmarket Close," by Ian Rankin, "Second Chance," by Danielle Steel, "State of Fear," by Michael Crichton, "Vince and Joy," by Lisa Jewel, "The Tinder Box," by Minette Walters, "Life Expectancy," by Dean Koontz, "The Magic Hour," by Charlotte Bingham.